2018
DOI: 10.1039/c8ra02930j
|View full text |Cite
|
Sign up to set email alerts
|

Free-standing polydopamine films generated in the presence of different metallic ions: the comparison of reaction process and film properties

Abstract: Different stratification processes lead to different morphologies of films generated with various cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…43,46 Incorporation of nonelectroactive metal ions has been reported to shift the point of zero charge downward by approximately one pH unit, and the authors attributed this to a higher amount of pyrrolecarboxylic acids, although without further justification. 43 On the other hand, copper has been reported to bring about an opposite and larger change. 46 With the nanoparticles prepared using the redox-active metal ions in this work, the ζ potential in acidic solutions was more negative than that of the purely autoxidized ones (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…43,46 Incorporation of nonelectroactive metal ions has been reported to shift the point of zero charge downward by approximately one pH unit, and the authors attributed this to a higher amount of pyrrolecarboxylic acids, although without further justification. 43 On the other hand, copper has been reported to bring about an opposite and larger change. 46 With the nanoparticles prepared using the redox-active metal ions in this work, the ζ potential in acidic solutions was more negative than that of the purely autoxidized ones (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…If the autoxidation of dopamine is carried out in the presence of various nonoxidizing metal ions (Na + , Ca 2+ , Mg 2+ , Co 2+ ), the nanoparticle formation and their properties are affected. 43 Fentonlike chemistry using a mixture of Fe(II) and hydrogen peroxide leads to a rapid generation of polydopamine nanoparticles. 44 On the other hand, oxidation of dopamine by Cu(II) under anaerobic conditions is a very slow reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Freestanding PDA films with a thickness of several hundreds of nanometers or even micrometers have been synthesized before. [ 20–27 ] Ultrathin and homogeneous PDA films attached to gold surfaces with thicknesses of 5–20 nm have been prepared by electropolymerization. [ 28 ] Electropolymerization is considerably faster than the often applied dip coating procedure, allowing precise control of the film thickness and homogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Polydopamine films formed at the air-water interface have attracted less attention [16,[23][24][25][26] as compared with the films on a solid substrate [27,28]. The application of pendant drop tensiometry showed that the surface tension decreased to 53 mN/m at a concentration of 2 g/l and to 10 mN/m at a concentration of 10 g/l [24].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the polydopamine film is far more extended than a monolayer, and one can measure only some effective surface tension, which can depend on the measurement method [29,30]. Even so, such films are characterized by weak durability, which can be improved by the addition of different agents such as urea, pyrochatechol, alginate catechol [25], poly(ethylene imine) [31], and metal ions [26]. Polymers work like cross-linkers creating covalent bonds between isolated polydopamine clusters.…”
Section: Introductionmentioning
confidence: 99%